Efficacy of Active Immunization With Attenuated α-Hemolysin and Panton-Valentine Leukocidin in a Rabbit Model of Staphylococcus aureus Necrotizing Pneumonia. (26th August 2019) - Tran, Vuvi G; Venkatasubramaniam, Arundhathi; Adhikari, Rajan P; Krishnan, Subramaniam; Wang, Xing; Le, Vien T M; Le, Hoan N; Vu, Trang T T; Schneider-Smith, Erika; Aman, M Javad; Diep, Binh An
Abstract: Staphylococcus aureus is a common pathogen causing infections in humans with various degrees of severity, with pneumonia being one of the most severe infections. In as much as staphylococcal pneumonia is a disease driven in large part by α-hemolysin (Hla) and Panton-Valentine leukocidin (PVL), we evaluated whether active immunization with attenuated forms of Hla (HlaH35L/H48L ) alone, PVL components (LukS-PVT28F/K97A/S209A and LukF-PVK102A ) alone, or combination of all 3 toxoids could prevent lethal challenge in a rabbit model of necrotizing pneumonia caused by the USA300 community-associated methicillin-resistant S. aureus (MRSA). Rabbits vaccinated with Hla toxoid alone or PVL components alone were only partially protected against lethal pneumonia, whereas those vaccinated with all 3 toxoids had 100% protection against lethality. Vaccine-mediated protection correlated with induction of polyclonal antibody response that neutralized not only α-hemolysin and PVL, but also other related toxins, produced by USA300 and other epidemic MRSA clones.